Determination of in situ NPK fertilization for rice growth in intensive farming system - Wijaya, Rahmi; Budianta, Dedik (Indonesian Soil Science Society of South Sumatra in Collaboration With Soil Science Department, Sriwijaya University, 2023)
Rice fields that were intensively cultivated by the application of chemical fertilizers for a long time may experience declining rice production, as the soil ages. Therefore, it is necessary to assess the fertility of the paddy soil for rice cultivation. Site-specific balanced fertilization is determined based on soil test results that represent the in situ soil chemical properties. This study aims to analyze the fertility level of paddy fields and determine the optimal amounts of nitrogen (N), phosphorus (P), and potassium (K) fertilizers for rice growth, considering the soil fertility status in Marga Cinta, Belitang Madang Raya District, Ogan Komering Ulu Timur of South Sumatra, Indonesia. The study employed a random sampling method, with a total of 6 samples collected by drilling at a depth of 0 - 30 cm, and then composited. The results revealed that the fertility of the paddy soil at the study site was relatively low, with an average pH of 5.32, organic carbon content (C-Organic) of 0.67%, cation exchange capacity (CEC) of 9.85 cmol/kg, base saturation of 21.05%, total nitrogen (N-total) of 0.10%, available phosphorus (P-available) of 1.87 mg/kg, and exchangeable potassium (K-exchangeability) of 0.10 cmol/kg. Based on these findings, the recommended fertilization amounts are 199.89 kg/ha of urea, 147.91 kg/ha of SP-36, and 28.45 kg/ha of KCl.